The Development of Lerpoche Learning Media for the Literaturgeschichte Course - Inggit Trisiana (Universitas Negeri Malang, 2020)
The aim of this research and development is to develop Lerpoche learning media for the Literaturgeschichte course. The research and development model used in this study is the Four-D development model (1974). This model is modified into three steps, namely (1) Define, (2) Design, and (3) Develop. In this study, data were obtained from the results of product validation by material experts and media experts. The result of this research and development is that Lerpoche learning media can be used in the Literaturgeschichte learning course.